2023
DOI: 10.1371/journal.pntd.0011713
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dengue incidence following city-wide wMel Wolbachia mosquito releases throughout three Colombian cities: Interrupted time series analysis and a prospective case-control study

Ivan Dario Velez,
Stephanie K. Tanamas,
Maria Patricia Arbelaez
et al.

Abstract: Background The introduction of Wolbachia (wMel strain) into Aedes aegypti mosquitoes reduces their capacity to transmit dengue and other arboviruses. Randomised and non-randomised studies in multiple countries have shown significant reductions in dengue incidence following field releases of wMel-infected Ae. aegypti. We report the public health outcomes from phased, large-scale releases of wMel-Ae. aegypti mosquitoes throughout three contiguous cities in the Aburrá Valley, Colombia. Methodology/Principal fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…While wMel introductions into Ae. aegypti have been very effective in locations where they have spread to high, stable frequencies (Hoffmann et al 2011;Utarini et al 2021;Lenharo 2023;Velez et al 2023)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While wMel introductions into Ae. aegypti have been very effective in locations where they have spread to high, stable frequencies (Hoffmann et al 2011;Utarini et al 2021;Lenharo 2023;Velez et al 2023)…”
Section: Discussionmentioning
confidence: 99%
“…CI facilitates the establishment of wMel in natural Ae. aegypti populations and successful biocontrol of dengue (Walker et al 2011;Utarini et al 2021;Lenharo 2023;Velez et al 2023) Here we focus on determining the timescale of divergence and evolution of Wolbachia closely related to wMel (Martinez et al 2021) and observed in holometabolous host species diverged about 350 MY. We present a new temporal calibration of Wolbachia divergence using cladogenically inherited Wolbachia.…”
Section: Analyses Of Model Drosophila Systems Have Made Fundamental C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Control and mitigation measures for DENV may impact the need for laboratory diagnostics. Control measures have had some recent successes, including the deployment of Wolbachia -infected mosquitos (which has significantly decreased infection rates in release areas) [17–23], and the development of vaccines [24–27]. Due to the risk of subsequent severe DENV infection related to ADE [28], vaccination is only recommended for those who have confirmed prior DENV infection, unless there is high local seroprevalence in the target age group for vaccination [27, 29].…”
Section: Introductionmentioning
confidence: 99%
“…In North Queensland, Australia, dengue incidence reduced nearly 65% during w Mel releases for 28 months between 2014 and 2017 and >95% 24 months after releases [ 27 ]. Another recent study in Colombia has shown that the Wolbachia deployments occurring since 2015 achieved an impressive dengue incidence decrease of 94–97%, with two out of the three cities that received the program being considered fully treated (60% of the local mosquitoes with Wolbachia [ 28 , 29 ]).…”
Section: Introductionmentioning
confidence: 99%